2018
DOI: 10.1038/s41398-018-0233-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation age is accelerated in alcohol dependence

Abstract: Alcohol dependence (ALC) is a chronic, relapsing disorder that increases the burden of chronic disease and significantly contributes to numerous premature deaths each year. Previous research suggests that chronic, heavy alcohol consumption is associated with differential DNA methylation patterns. In addition, DNA methylation levels at certain CpG sites have been correlated with age. We used an epigenetic clock to investigate the potential role of excessive alcohol consumption in epigenetic aging. We explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 36 publications
7
64
0
2
Order By: Relevance
“…Lower values of age-adjusted DNAm TL are hypothesised to correlate with poorer health as this reflects shorter telomere length. To date, a number of studies have demonstrated associations between epigenetic measures of ageing and risk of mortality and disease states [21][22][23][24] or have provided comparisons of such epigenetic measures [25][26][27][28][29][30]. However, no study has compared all six epigenetic measures of ageing with respect to their association with a broad range of common health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lower values of age-adjusted DNAm TL are hypothesised to correlate with poorer health as this reflects shorter telomere length. To date, a number of studies have demonstrated associations between epigenetic measures of ageing and risk of mortality and disease states [21][22][23][24] or have provided comparisons of such epigenetic measures [25][26][27][28][29][30]. However, no study has compared all six epigenetic measures of ageing with respect to their association with a broad range of common health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These biomarkers have been proposed as accurate and robust biomarkers of aging, but also as indicators of the biological health of an individual: DNAm age, also known as epigenetic age, measured in blood cells, has been found to be predictive of mortality (Marioni et al 2015a;Perna et al 2016;Christiansen et al 2016;Chen et al 2016;Dugué et al 2018) and other aging-related outcomes such as frailty (Breitling et al 2016) or cognitive and physical functioning (Marioni et al 2015b;Degerman et al 2017;Simpkin et al 2017;Gale et al 2018a;Sillanpää et al 2018). Recent studies demonstrated that age-associated epigenetic variations can be affected by diet (Bacalini et al 2014;Kok et al 2015;Quach et al 2017) and that exposure to some pathogenic conditions or environmental factors can influence DNAm age (Horvath et al 2014;Nevalainen et al 2017;Li et al 2018;Rosen et al 2018); however, little is known about the specific relationship between nutritional interventions and epigenetic biomarkers of aging.…”
Section: Introductionmentioning
confidence: 99%
“…(Kaminsky, Assadzadeh, Flanagan, & Petronis, 2005). rDNAm age acceleration, was estimated by the residuals of regressing the DNAm age on the chronological age (which was determined calculated by subtracting the date of inclusion from the date of birth, divided by 365.25 days, taking leap years into account) (Rosen et al, 2018).…”
Section: Determination Of the Residual Dnam (Rdnam) Age Accelerationmentioning
confidence: 99%